1998
DOI: 10.1203/00006450-199804000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Early Activation Events in Cord Blood B Cells after Stimulation with T Cell-Independent Activators

Abstract: Human neonates are immunologically immature, particularly in their humoral antibody responses to T cell-independent antigens, as exemplified by their increased susceptibility to infections with polysaccharide-encapsulated bacteria. To clarify the mechanism(s) underlying the unresponsiveness of neonates to polysaccharide antigens, we used an in vitro model with neonatal cord blood cells that has been shown to mimic surface Ig-dependent signaling in the adult by T cell-independent antigens. We studied the abilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 43 publications
1
8
0
Order By: Relevance
“…35,64 Further expansion of CD27 1 MBCs during the first year of life occurred in parallel with an increased proportion of CD21 2 (C3d receptor) MBCs with a limited ability to respond to polysaccharide-complement complexes. 65,66 The fact that within naive B cells the percentage of CD21 2 cells remains stable with age and shows a comparable in vitro response to polysaccharide antigens in children and adults 67 suggests that external factors affecting antigen recognition might increase the production of C3d receptor-deficient MBCs in children of around 1 year of age when serum C3 levels reach adult-like values. 68 Thus the limited availability of C3d and C3d-antigen complexes in infants less than 1 year old because low serum C3 levels 69 might contribute to reduced signaling for expression of this receptor during antigen recognition.…”
Section: Discussionmentioning
confidence: 99%
“…35,64 Further expansion of CD27 1 MBCs during the first year of life occurred in parallel with an increased proportion of CD21 2 (C3d receptor) MBCs with a limited ability to respond to polysaccharide-complement complexes. 65,66 The fact that within naive B cells the percentage of CD21 2 cells remains stable with age and shows a comparable in vitro response to polysaccharide antigens in children and adults 67 suggests that external factors affecting antigen recognition might increase the production of C3d receptor-deficient MBCs in children of around 1 year of age when serum C3 levels reach adult-like values. 68 Thus the limited availability of C3d and C3d-antigen complexes in infants less than 1 year old because low serum C3 levels 69 might contribute to reduced signaling for expression of this receptor during antigen recognition.…”
Section: Discussionmentioning
confidence: 99%
“…␣-␦-dex consists of high-molecular-weight dextran polysaccharide carrier molecules, which are coupled to polyclonal anti-IgD antibodies that can induce a multivalent stimulus to B cells [26,27]. The concentration of ␣-␦-dex [26,28] used was 1 g/ml.…”
Section: Cell Stimulationmentioning
confidence: 99%
“…In particular, while ligation of the B cell antigen receptor (BCR) induces MHC Class II up‐regulation and proliferation in mature adult B cells, neonatal B cells fail to hyperexpress MHC class II [11] and are induced to undergo apoptosis by this stimulus [12]. In contrast to these murine studies, some authors have shown that human cord blood B cells can respond positively to cross‐linking of the antigen receptor [13–15].…”
Section: Introductionmentioning
confidence: 99%